Les ittifâq-s communautaires. Escamotage d’archives et autonomie locale dans la province de Tunis au XIXe siècle - Sami Bargaoui (L’Année du Maghreb)
In this work, the author examines a batch of Tunisian archives from the modern era, not listed and never made available to researchers. By focusing on the production and archiving processes of these documents – election certificates (ittifâq-s) to public offices in local communities often involving very large sections of men – he questions the dominant gaze in the historiography of the province which, by adopting a state point of view, greatly amplifies the reality of the hegemony of central power and minimizes the role of local agents. The invisibilization of these archives participated in the construction of the image of a territorial and national state that was built by the dissolution of local authorities and the advent of a "modern" political subject, whereas in fact, local communities have integrated themselves into the global political body while retaining a relative autonomy which at least allows them to choose themselves those who govern them in the places where they live.